Fenomenologia della “situazione musicale”. Note sul “problema dell’ascolto” in Günther Anders e Theodor W. Adorno - Adussi, Filippo (Scenari, 2024)
Since his philosophical debut, Günther Anders – at the time known as Günther Stern – developed an original “phenomenology of listening” which criticized the Husserlian approach. In order to work in Frankfurt with Adorno, Anders elaborates a musicology of “situationality” as his research project. Unfortunately, Adorno will consider this perspective “too Heideggerian”, rejecting it. It is the moment that marks a philosophical crossroads: on the one hand the listening interpreted by Anders as a phenomenon situated in space, on the other hand Adorno’s sociological perspective, which criticizes the regressed listener and the “musical fetishism”. If Adorno is certainly one of the most famous detractors of “jazz music” as a commercial “pop” phenomenon, Anders’ diagnosis of “antiquated” (Antiquiertheit) listening leads this question in another direction: what meaning can contemporary music still have in the era of the “obsolescence” of human beings?